Mastering Manga Studio 5 : an extensive, fun, and practical guide to streamlining your comic-making workflow using Manga Studio 5 /: an extensive, fun, and practical guide to streamlining your comic-making workflow using Manga Studio 5. (2013) - Unknown
No abstract available